Omission of quality assurance during data entry in public health research from India: Is there an elephant in the room? - Nafis Faizi; Ajay M Kumar; Shahwar Kazmi (Wolters Kluwer Medknow Publications, 2018)
As the adage, "Garbage in, Garbage out" goes, data entry errors may lead to erroneous results and conclusions. Quality assurance during data entry is one of the most neglected components of research and is conspicuously missing in most of the reporting standards. In this study, we reviewed research studies published in Indian Journal of Public Health and Indian Journal of Community Medicine during 2014-2016 and determined the proportion of papers reporting on quality assurance during data entry. Of 110 papers, only 6 (5.5%) papers explicitly included a statement about data quality assurance, with two studies reported to have performed double entry and validation, considered the gold standard in quality-assurance of data entry. This is highly unacceptable. We hereby appeal to the community of researchers, peer reviewers, and journal editors in India to pay attention to this important aspect of research and make reporting of quality assurance of data entry mandatory in every published paper.